While you were sleeping (Hollywood Pictures Home Video, 1998)
In Chicago, a subway employee is in love with a stranger she only sees from a distance. But when she rescues him from a mugging in which he is knocked into a coma, his family mistakes her for his fiancee. When she falls for his charming brother, the mix-up escalates.